(untitled) (Journal of Asian Development Studies, 2025)
This study was conducted in Lulusar Dudipatsar National Park Kaghan Valley. The purpose of the study is to explore the livelihood assets of inhabitants of the study area. Therefore; livelihood assets of the study area were studied. The study area is dominated by three communities namely agro-pastoralists, pastoralists and nomads. All the three communities are depended on available assets and follow seasonal migration to utilize the seasonally available resources. They move up hill in summer and down to plain areas in winter. The livelihood of agro-pastoralists is depended on cash crop production, livestock and tourism related activities. The agriculture land is limited and crops are grown on terraces dug on hilly slopes. The livelihood of pastoralists and nomads is depended on herds (i.e. goats and sheep) and pastures availability. They keep large number of livestock. The study is based on primary data collection through questionnaires, interviews and groups discussion. Content analysis technique was applied for analyzing questionnaires and groups discussion. Conceptual analysis was applied for questionnaires to establish frequencies of the concepts while relational analysis was applied for groups discussion to establish relationship among different concepts. The study contributes to theoretical understandings of the Sustainable Livelihoods Framework (SLF), highlighting how access to the five capitals—natural, human, physical, social, and financial—shapes the choice of livelihood strategies in mountainous terrain. Chi-square analysis, narrative accounts, and spatial mapping tools were used to identify these variations.